2015
DOI: 10.1007/s10195-014-0332-9
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary nailing versus proximal plating in the management of closed extra-articular proximal tibial fracture: a randomized controlled trial

Abstract: BackgroundExtra-articular proximal tibial fractures account for 5–11 % of all tibial shaft fractures. In recent years, closed reduction and minimally invasive plating and multidirectional locked intramedullary nailing have both become widely used treatment modalities for proximal and distal tibial metaphyseal fractures. This study was performed to compare plating and nailing options in proximal tibia extra-articular fractures.Materials and methodsThis randomized prospective clinical study was conducted on 58 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 23 publications
3
45
0
Order By: Relevance
“…#Union Min Max Mean Rate % p-value wrt present VIDYADHARA S et al [1] 12 36 17.2 0.1626 LINDVALL E et al [16] 96 MEENA RC et al [2] 10 30 18.26 94.7 0.1809 PRESENT 12 18 Pain: Present study reported moderate Knee Pain in 7 cases.…”
Section: Closed/openmentioning
confidence: 66%
See 4 more Smart Citations
“…#Union Min Max Mean Rate % p-value wrt present VIDYADHARA S et al [1] 12 36 17.2 0.1626 LINDVALL E et al [16] 96 MEENA RC et al [2] 10 30 18.26 94.7 0.1809 PRESENT 12 18 Pain: Present study reported moderate Knee Pain in 7 cases.…”
Section: Closed/openmentioning
confidence: 66%
“…After the end of 6 months follow up most of the patients showed excellent results (12patients, 60%), 5 patients (25%) falls under good category, 3 patients (15%) showed fair results and none of patient showed poor results. [1] 18 67 43 Nork Se et al [15] 19 73 42 Lindvall E et al [16] 18 60 36.41 Meena Rc et al [2] 18 65 39 Present 19 60 33.6…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations